Chalcogen bonding interactions in organic selenocyanates: from cooperativity to chelation. (12th March 2018) - Jeannin, Olivier; Huynh, Huu-Tri; Riel, Asia Marie S.; Fourmigué, Marc
Abstract : Organic selenocyanates form recurrent chain-like motifs ⋯Se(R)–CN⋯Se(R)–CN⋯ through short and linear chalcogen bonding Se⋯NC interactions. A chelating motif is also observed in a DMF solvate with two neighboring CH2 –SeCN groups linked to the DMF oxygen atom. Abstract : Intermolecular chalcogen bonding interactions are identified in crystalline organic selenocyanates where a linear Se⋯NC interaction takes place, leading to the recurrent formation of chain-like motifs ⋯Se(R)–CN⋯Se(R)–CN⋯, stabilized by cooperativity. Analysis of 15 reported structures of such selenocyanates is complemented by the structural determinations of three other novel polytopic selenocyanates, namely 1, 3, 5-tris(selenocyanatomethyl)benzene (1a ), 1, 3, 5-tris(selenocyanatomethyl)-2, 4, 6-trimethylbenzene (1b ) and 1, 2, 4, 5-tetrakis(selenocyanatomethyl)benzene (2 ). While the recurrent chain-like motifs with short and linear Se⋯N contacts are indeed observed in the pure compounds, solvates with DMF and AcOEt also demonstrate that the nitrile N atom can be easily displaced from the chalcogen bond by stronger Lewis bases such as carbonyl oxygen atoms, leading in the case of (2 )·(DMF)2 to a chelating motif where two neighboring CH2 –SeCN groups link to the same oxygen atom through Se⋯O interactions.